Cardiorenal syndrome type 1 in the cardiology intensive care unit - Savic, Lidija; Matic, Dragan; Milosevic, Aleksandra (Medical Research, 2026)
The kidneys and the heart are closely connected, and the dysfunction or failure of one organ often leads to the dysfunction or failure of the other. This condition is known as cardiorenal syndrome. There are five types of cardiorenal syndrome (CRS), categorized by the primarily failing organ (the kidneys or the heart) and whether the failure is acute or chronic. CRS type 1 (CRS-1) is defined as acute kidney injury (AKI) caused by acute heart failure (AHF). CRS-1 develops in more than 30% of patients hospitalized in the cardiology intensive care unit (CICU). The aim of this narrative review is to present the pathophysiological mechanisms, therapeutic implications and prognostic significance of CRS-1 in patients hospitalized in the CICU. The mechanisms of CRS-1 development are complex. They include low cardiac output and venous congestion with subsequent neurohumoral activation and inflammation. Since the hallmark of CRS-1 is diuretic resistance, the development of CRS-1 complicates the treatment strategy in acutely decompensated patients, and strongly and negatively affects patients’ short- and long-term outcomes. For clinicians, early identification of patients at risk of developing CRS-1 is essential, along with timely adjustment of the therapeutic approach to achieve optimal decongestion, prevent CRS-1 progression, and improve both short- and long-term prognosis.